Jamaica : Selected Issues. (IMF Staff Country Reports; Country Report, 1999)
This Selected Issues paper presents an overview of financial system developments in Jamaica. The financial system experienced substantial growth over 1989-95 as a result of the liberalization of financial markets and the reduction in government involvement in the industry through the privatization of banks. The paper highlights that banks that had been acquired by the government in the 1970s were sold back to the private sector. This paper also reviews developments in monetary policy in Jamaica, and the role of the public sector.